2014
DOI: 10.1371/journal.pone.0096091
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of the Polyphenol Sesamin on Allergen-Induced TH2 Responses and Airway Inflammation in Mice

Abstract: Allergic asthma is a lifelong airway condition that affects people of all ages. In recent decades, asthma prevalence continues to increase globally, with an estimated number of 250,000 annual deaths attributed to the disease. Although inhaled corticosteroids and b-adrenergic receptor agonists are the primary therapeutic avenues that effectively reduce asthma symptoms, profound side effects may occur in patients with long-term treatments. Therefore, development of new therapeutic strategies is needed as alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 65 publications
2
22
0
Order By: Relevance
“…Therefore, targeting inflammatory pathways may provide effective therapeutic intervention for treatment of acute ischemic stroke. Recent studies have shown the potential anti-inflammatory properties of SES against neuroinflammation and inflammatory mediators (Bournival et al, 2012b;Lin et al, 2014). In agreement with these investigations, our results indicated that SES treatment suppressed TNF-a and IL-6 mRNA levels in ischemic brain and therefore may act as anti-inflammatory agent.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, targeting inflammatory pathways may provide effective therapeutic intervention for treatment of acute ischemic stroke. Recent studies have shown the potential anti-inflammatory properties of SES against neuroinflammation and inflammatory mediators (Bournival et al, 2012b;Lin et al, 2014). In agreement with these investigations, our results indicated that SES treatment suppressed TNF-a and IL-6 mRNA levels in ischemic brain and therefore may act as anti-inflammatory agent.…”
Section: Discussionsupporting
confidence: 91%
“…Sesamin (SES) is one of the most abundant ligand in sesame seeds (Phitak et al, 2012). It has been shown to exhibit multiple biological functions, such as inhibition of inflammation (Lin et al, 2014), carcinogenesis (Deng et al, 2013) and oxidative stress (Hsieh et al, 2011). In addition, sesamin has been reported to attenuate hypertension (Matsumura et al, 1995), serum and hepatic cholesterol (Hirata et al, 1996), serum triglycerides (Fukuda et al, 1998), cerebral thrombogenesis (Noguchi et al, 2004), and neuroinflammation (Bournival et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…A few cereal lignans have also been tested in vitro and found to be effective inhibitors of adipocyte differentiation. Pinoresinol, cycloisolariciresinol, lariciresinol, seicoisolariciresinol in the concentration range of 1-1000 nM, are effective in inhibiting 3T3-L1 cell differentiation [77] and although their fine mechanism of action has still to be clarified, it is likely that it involves the ability to regulate nuclear receptors such as PPARs, ERs and LXRs [65,78,79].…”
Section: Mechanisms Of Lignans On Healthmentioning
confidence: 99%
“…The severity of inflammatory cell infiltration was determined by a 5-point system with scoring as follows: 0, none (no inflammation); 1, minimal (occasion ruffing with inflammatory cells); 2, mild (1-3 cells); 3, moderate (4-5 cells); and 4, severe (more than 5 cells). 50 Goblet cell hyperplasia was quantified using 5-point system with scoring as follows: 0, no goblet cells; 1, <25% goblet cells in cell population; 2, 25-50%; 3, 50-75%; and 4, > 75% of goblet cells. 51 Western blot analysis RAW264.7 cells were harvested and inoculated into T25 flasks at a density of 2 9 10 5 cells/flask.…”
Section: Histological Examinationmentioning
confidence: 99%